Cardiorespiratory Endurance on College Student Smokers Using Harvard Step Test - Agustina, Rismia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Purpose: The aim of this research was to identify the score of Harvard Step Test as indicator ofcardiorespiratory endurance on college student smokers. Method: This was a descriptive cross-sectionalstudy. There were 40 samples who met inclusion and exclusion criteria were selected using purposivesampling. The instruments of this study were questionnaire, metronome, stop watch, and 19 inches bench.Data were analyzed using descriptive statistics. Results: The results showed that 47,5% of subjects had poorlevel, 42,5% had average level, and 10% had good level of Harvard step test. On average, 65% of subjectswere light smokers, 87,5% were filtered cigarette smokers, and 65% had been smoking for 2-5 years.Conclusion: It can be concluded nearly half of college student smokers had poor Harvard step test score asindicator of cardiorespiratory endurance.